proposition d'un Algorithme de segmentation de la voie arabe à base de spectrogrammes - Guediri, abderrahmane; hakkoum, abdelaziz (جامعة الوادي University of Eloued, 2019)
"تتزايد أهمية استخدام الحاسبة في شتى مجالات الحياة، ولعله لم يحدث من قبل أن تطور علم من العلوم كما تطور علم الحاسبات خلال السنوات الثلاثين الأخيرة وخاصة في مجال الذكاء الصناعي الذي عرف تقدما باهرا وخاصة في مجال التعرف على الكلام ومعالجته. سنركز في هذه الأطروحة على التعرف التلقائي للصوت المأخوذ من خلال الميكروفون والذي يتم تحويله الى نص من قبل الجهاز، وللقيام بهذه العملية سنمر بعدة خطوات (قبل المعالجة، التقسيم، استخراج الخصائص، التصنيف والتعرف) بغية الوصول الى النتيجة النهائية، وركزنا في عملنا هذا على مرحلة التقسيم واستخراج الخصائص والتصنيف وهي الأهم في العملية. لسوء الحظ الأساليب المتبعة والمستخدمة في تقسيم الكلام للغات الأجنبية (الإنجليزية، الفرنسية،... الخ) لا تتوافق كليا مع اللغة العربية نظرا للاختلاف الكبير بين هذه الأخيرة وغيرها من اللغات ، لذلك توجب علينا اقتراح طرق وأساليب جديدة لمعالجة هذا المشكل, وهو ما قمنا به . الطريقة التي قمنا باقتراحها أعطت نجاعة كبيرة في التقسيم في زمن وجيز مقارنة بالطرق الأخرى."The use of computers in various fields of life has become increasingly important. Maybe it has never been any equal development to the one of computer science in the last 30 years, especially in the field of artificial intelligence, which has made remarkable progress. Specifically, Speech Recognition and Treatment field. In our memory, we will focus on the automatic recognition of the sound captured by the microphone which is to be converted into text by the system. To perform this process we will take several steps (Preprocessing, Segmentation, Feature Extraction, Classification and Recognition) in order to reach the final result. Segmentation, Feature Extraction and Classification stages are the most important in our procedure. Unfortunately, the methods used in the Division for a speech in a foreign language (English, French, etc.) are not entirely compatible with Arabic because of the radical difference between this latter and other languages. Therefore, we have to propose new ways and methods to address this problem, and we have. The method we proposed gave promising results for the segmentation and in a short time compared to other methods." "
mémoire master informatique
Keywords: التقسيم، التصنيف ، التعرف الالي للكلام، نجاعة كبيرة في التقسيم; Segmentation, Classification,Automatic speech recognition, very efficient segmentation.